HIV care and treatment models and their association with medication possession ratio among treatment‐experienced adults in three African countries. Issue 11 (8th August 2021) - Tsui, Sharon; Kennedy, Caitlin E.; Moulton, Lawrence H.; Chang, Larry W.; Farley, Jason E.; Torpey, Kwasi; van Praag, Eric; Koole, Olivier; Ford, Nathan; Wabwire‐Mangen, Fred; Denison, Julie A.
Abstract: Objective: How clinics structure the delivery of antiretroviral therapy (ART) services may influence patient adherence. We assessed the relationship between models of HIV care delivery and adherence as measured by medication possession ratio (MPR) among treatment‐experienced adults in Tanzania, Uganda and Zambia. Methods: Eighteen clinics were grouped into three models of HIV care. Model 1‐Traditional and Model 2‐Mixed represented task‐sharing of clinical services between physicians and clinical officers, distinguished by whether nurses played a role in clinical care; in Model 3‐Task‐Shifted, clinical officers and nurses shared clinical responsibilities without physicians. We assessed MPR among 3, 419 patients and calculated clinic‐level MPR summaries. We then calculated the mean differences of percentages and adjusted residual ratio (aRR) of the association between models of care and incomplete adherence, defined as a MPR <90%, adjusting for individual‐level characteristics. Results: In the adjusted analysis, patients in Model 1‐Traditional were more likely than patients in Model 2‐Mixed to have MPR <90% (aRR = 1.60, 95% CI 1–2.48). Patients in Model 1‐Traditional were no more likely than patients in Model 3‐Task‐Shifted to have a MPR <90% (aRR = 1.58, 95% 0.88–2.85). There was no evidence of differences in MPR <90% between Model 2‐Mixed and Model 3‐Task‐Shifted (aRR = 0.99, 95% CI 0.59–1.66). Conclusion: Non‐physician‐led ART programmes were associated with adherence levels as good as or better than physician‐led ART programmes. Additional research is needed to optimise models of care to support patients on lifelong treatment.